Uporaba instituta suspenzivnega veta v primeru zakonov o nujnih ukrepih za zagotovitev obrambe države, varnosti ali odprave posledic naravnih nesreč - Ahmetović, Aldijana (Pravnik, 2023)
In 2020, the Slovenian legislator amended the Referendum and Popular Initiative Act to provide for a special procedure related to a call for a legislative referendum in the case of laws on urgent measures to ensure state defence, security, or the elimination of the consequences of natural disasters. Because the legislator main goal was to expedite the law implementation process it inadequately regulated the powers of the National Council, particularly the right to file a suspensive veto. The author discusses some of the constitutional dilemmas related to the institute of the suspensive veto which arose after the adoption of Article 21.a of the Referendum and Popular Initiative Act. Based on the analogy with the limitation of the legislative referendum and the comparative analysis the author offers possible solutions for the arrangement of the institute of the suspensive veto in the case of such legislation. These solutions would address not only the need to ensure faster promulgation of legislation but also the need to constitutionally regulate the limitation of the suspensive veto of the National Council.
Keywords: Državni svet; Državni zbor; odložilni veto; retroaktivnost; ustavno pravo; zakonodaja; zakonodajni postopek; zloraba pravice